Something big has been here - Prelutsky, Jack; Stevenson, James, 1929- (New York : Greenwillow Books, 1990)
An illustrated collection of humorous poems on a variety of topics.
Includes indexes.
Keywords: Children's poetry, American; American poetry; Humorous poetry